An engineered macroencapsulation membrane releasing FTY720 to precondition pancreatic islet transplantation. Issue 2 (27th February 2017) - Bowers, Daniel T.; Olingy, Claire E.; Chhabra, Preeti; Langman, Linda; Merrill, Parker H.; Linhart, Ritu S.; Tanes, Michael L.; Lin, Dan; Brayman, Kenneth L.; Botchwey, Edward A.
Abstract: Macroencapsulation is a powerful approach to increase the efficiency of extrahepatic pancreatic islet transplant. FTY720, a small molecule that activates signaling through sphingosine‐1‐phosphate receptors, is immunomodulatory and pro‐angiogenic upon sustained delivery from biomaterials. While FTY720 (fingolimod, Gilenya) has been explored for organ transplantation, in the present work the effect of locally released FTY720 from novel nanofiber‐based macroencapsulation membranes is explored for islet transplantation. We screened islet viability during culture with FTY720 and various biodegradable polymers. Islet viability is significantly reduced by the addition of high doses (≥500 ng/mL) of soluble FTY720. Among the polymers screened, islets have the highest viability when cultured with poly(3‐hydroxybutyrate‐co‐3‐hydroxyvalerate) (PHBV). Therefore, PHBV was blended with polycaprolactone (PCL) for mechanical stability and electrospun into nanofibers. Islets had no detectable function ex vivo following 5 days or 12 h of subcutaneous implantation within our engineered device. Subsequently, we explored a preconditioning scheme in which islets are transplanted 2 weeks after FTY720‐loaded nanofibers are implanted. This allows FTY720 to orchestrate a local regenerative milieu while preventing premature transplantation into avascular sites that contain high concentrations of FTY720. These results provide a foundation and motivation for further investigation into the use of FTY720 in preconditioning sites for efficacious islet transplantation. © 2017 Wiley Periodicals, Inc. J Biomed Mater Res Part B: Appl Biomater, 106B: 555–568, 2018.